Private equity investment committee paper on Sogrape, S.A. investment thesis & business plan - Gonçalves, Fernando Jorge Acácio (2020)
This work project aims to study a private equity deal using a Leverage Buy out Model of the Portuguese company Sogrape, operating in the win sector. The evaluation of the deal includes the studying of the company and the inherent industry, followed by the description of the investment thesis and the business plan. Then, it is performed a valuation of the company by several methods such as the Discounted Cash Flow, Comparables Multiples and Precedent Transaction Multiples. Later, it is defined the capitals tructure of the deal, particularly both sources and uses. Next, it is presented the returns for the management and the fund, subject to a sensibility analysis taking in to account the various model in puts. To conclude it is evaluated the different exit options regarding the attractiveness and like lihooda long with the different matters to be further studied in a due diligence. In this specific part is defined the investment thesis and the forecasted business plan for the next 7 years. The starting point was the market and company analysis where it was concluded it is needed to take advantage of Sogrape’s positioning as a leader in the Portuguese market, promoting consolidation through an acquisition and empower the company positioning as a distributor. Regarding the international markets, partof the strategy involves to change the route-to-marketin USA ,akey market to this sector. In the other market clusters as growth platformss and mature markets ,the plan involves the promotion of sales through an increase in marketing expenses as well as focusing on the segments tha tis expected to face a higher growth rate in the following years and where Sograpeholds more competitive advantages such as ligh twines. This strategy also involves costreduction duetos ynergies coming from the above mentioned acquisition .In the presented in vestment case, from the entry year of 2020 until the exitin 2026, there venues have a CAGR of 12% while EBITDA is growing at 15%CAGR.